MADRASAH DEVELOPMENT PLAN MTS AL-WASHLIYAH BUILDING - Wijaya, Candra; Yunus, Muhammad; Hanum Nst, Rosida; Sahana, Willi (Universitas Dharmawangsa, 2020)
Madrasas as one of the educational institutions must be able to meet the demands of the times and be able to show their existence as a controller of change. Madrasas must continue to develop its institutions with strategies and management that can effectively produce quality education output. Then the madrasa must also have a new vision and mission, and be equipped with adequate facilities, management, and teaching staff who are better trained so that it can improve the status of the madrasa as a model school and become a model for the development standards of all other madrasas in Indonesia